Horizon scanning for potential invasive non‐native species across the United Kingdom Overseas Territories. Issue 1 (28th November 2022) - Dawson, Wayne; Peyton, Jodey M.; Pescott, Oliver L.; Adriaens, Tim; Cottier‐Cook, Elizabeth J.; Frohlich, Danielle S.; Key, Gillian; Malumphy, Chris; Martinou, Angeliki F.; Minchin, Dan; Moore, Niall; Rabitsch, Wolfgang; et al.
Abstract: Invasive non‐native species (INNS) are recognized as a major threat to island biodiversity, ecosystems, and economies globally. Preventing high‐risk INNS from being introduced is the most cost‐effective way to avoid their adverse impacts. We applied a horizon scanning approach to identify potentially INNS in the United Kingdom Overseas Territories (OTs), ranging from Antarctica to the Caribbean, and from the Pacific to the Atlantic. High‐risk species were identified according to their potential for arrival, establishment, and likely impacts on biodiversity and ecosystem function, economies, and human health. Across OTs, 231 taxa were included on high‐risk lists. The highest ranking species were the Asian green mussel ( Perna viridis ), little fire ant ( Wasmannia auropunctata ), brown rat ( Rattus norvegicus ), and mesquite tree ( Prosopis juliflora ). Shipping containers were identified as the introduction pathway associated with the most species. The shared high‐risk species and pathways identified provide a guide for other remote islands and archipelagos to focus ongoing biosecurity and surveillance aimed at preventing future incursions.